Does Exotic Dancing Lead to Prostitution? An Exploratory Study. Issue 1 (2nd January 2023) - Liles, Sandy; Blumberg, Elaine; Navala, Jennifer; Zellner, Jennifer; deTar, Laura; Nguyen, Ben; Robusto, Kristi; Kelley, Norma; Benedict, Cody; Zhang, Sheldon; Hovell, Mel
ABSTRACT: This study explored contextual variables within strip clubs employing exotic dancers as well as dancers' characteristics, as potential correlates of prostitution. Face-to-face anonymous interviews were conducted with exotic dancers in San Diego County (N = 123). Logistic regression revealed that nonwhite race, allowing customer touching, illegal drug use, and number of dances per shift were significant predictors of prostitution, while childhood neglect and abuse in adulthood were near-significant. Exotic dancers may be at elevated risk for engaging in prostitution, though results warrant further quantitative research, including early intervention studies for prevention/reduction of prostitution practices and sexually transmitted infections (STIs).